Nowoczesna archeologia Profesora Jana Żaka (1923-1990). W 100. rocznicę urodzin - Minta-Tworzowska, Danuta (Folia Praehistorica Posnaniensia, 2023)
On March 23rd, 2023 the 100th anniversary of Professor Jan Żak’s birth was marked with an exhibition and a seminar meant to present the modern archeology he had been creating. In addition to Professor’s scientific achievements, there were fragments presented of three documentaries to illustrate his involvement into popularization of archeology. The article discusses also Professor’s work and scientific activities in the field of early medieval archeology, methodology of archaeology and general prehistory, widely recognized and appreciated not only in Poland but also abroad. In 1945 Jan Żak took part in the military operations of the 3rd Carpathian Rifle Division, and his professional life took place in the realities of the People’s Republic of Poland. Particularly important were his organizational achievements as well as scientific contacts with researchers from Western Europe. The article also presents the direction of contemporary archeology methodology established by J. Żak, continued by his students and subsequent generations or archaeologists.